Efficient depolymerization of Kraft lignin to liquid fuels over an amorphous titanium-zirconium mixed oxide supported partially reduced nickel-cobalt catalyst. (July 2019) - Zhu, Chaofeng; Dou, Xiaomeng; Li, Wenzhi; Liu, Xiaohao; Li, Qingqing; Ma, Jianru; Liu, Qiying; Ma, Longlong
Graphical abstract: Highlights: Synergistic effect among Lewis acid sites, basic sites and metal active sites. Maximally 80.2% of monomeric and dimeric degradation products was obtained. The HHV of liquid product was increased from 25.11 to 33.89 MJ/kg. NiCo-NiCoOx /Ti1−y Zry O2 catalyst exhibits excellent recyclability. Abstract: A series of non-precious metal/metal oxide nickel-cobalt catalysts was prepared for a highly efficient depolymerization of Kraft lignin (KL) into liquid fuels using amorphous TiZr-oxide (Ti1−y Zry O2 ) as a carrier. The effects of Ni-NiOx, Co-CoOx, NiCo-NiCoOx, NiCoOx and NiCo catalysts supported on amorphous TiZr-oxide carrier on KL depolymerization were investigated. It was found that the NiCo-NiCoOx /Ti1−y Zry O2 catalyst is optimal for converting KL to petroleum ether (PE)-soluble product (mainly composed of monomers and dimers) in an 80.2% high yield at 320 °C for 24 h, with excellent reusability and a low formation of char. Under these conditions, the higher heating value (HHV) increased from 25.11 to 33.89 MJ/kg. A meticulous study on NiCo-NiCoOx /Ti1−y Zry O2 catalysts revealed that the synergistic effect among Lewis acid sites, basic sites and metal active sites played an important role in obtaining high yields of monomers and low rates of char formation during lignin conversion.